ISOLASI FUNGI ENDOFITIK PADA ORGAN KULIT AKAR TANAMAN GAMBIR (Uncaria guianensis) - Almaratus Shalehah; Rosela Amalia; Adelia Rosa; Agnes Elva Royani; Arlin Ramasari; Siti Mariyah Ulpah; Ummi Hiras Habisukan (Jurnal Inovasi Pendidikan dan Sains, 2023)
Gambier (Uncaria guanensis) is one of the non-timber forest products that has long been known and widely used by the community. Gambier is used as a tanner to prevent decay, making the skin softer, colored, not stiff and durable. Besides being used as a remedy for stomach pain, ulcers, and throat. The use of gambier is commonly known in eating betel as a mixture of ingredients to enhancer delicious taste. At the time of eating it tastes bitter but then tastes sweet and can nourish the teeth, gums, gums and throat. This study aims to isolate and identify the genus of endophytic fungi in gambier plants. The method used in this study was sampling the root bark of gambier plants. Making media using instant PDA media mixed with aquadest and antibiotics. Isolation of indophytic fungi in gambier plants is carried out by direct planting techniques, identification of endophytic fungi is carried out by microscopic and macroscopic observations. Macroscopic identification is done by observing, colony color, colony texture, shape (concentric or not) whereas microscopic can be done using a microscope. In microscopic observations, the presence or absence of sects in hyphae hyphal development, hyphal color, and conodia are all observed under a microscope using the slide culture method.